Preparation, identification and in vivo study of antioxidant peptides from Haematococcus pluvialis residue - Zhang, Yuling; Zhu, Mengjia; Zhou, Qingxin; Yang, Yuhong; Du, Lei; Gao, Xiang (Food bioscience, 2025)
Haematococcus pluvialis (H. pluvialis) residue is a by-product of astaxanthin extraction and has not been sufficiently utilized. Herein, we aimed to prepare novel antioxidative peptides from H. pluvialis residue (HPRP) and evaluate the ameliorative effects of HPRP on liver injury in D-Gal induced aging mice. The results indicated that neutral protease was the best protease and the optimal enzymatic conditions was determined. Peptides fractions with molecular weights below 5 kDa (HPRP-1) showed better antioxidant activity and excellent stability. Animal studies indicated that HPRP-1 and HPRP alleviated D-Gal-induced liver tissue oxidative injury. Potential mechanisms were the regulation of hepatic Keap1-Nrf2/HO-1 pathway and regulation of intestinal microbiota. Finally, three novel peptides (GVFHPGPF, IDPGTWRPL and APIIGKPAPGFK) with high antioxidant activity were screened based on LC-MS/MS, molecular docking and in vitro activity validation. Our findings provide new insights into the high-value utilization of H. pluvialis residue and exploitation of novel antioxidant functional ingredients. [Display omitted] •Enzymatic process for antioxidative peptides from H. pluvialis residue were optimized.•HPRP-1 (MW < 5 kDa) showed better antioxidant activity and excellent stability.•HPRP-1 alleviated hepatic injury, oxidative stress and inflammation in aging mice.•Regulation of hepatic Keap1-Nrf2 pathway and gut microbiota were potential mechanisms.•Three novel antioxidant peptides (GVFHPGPF, IDPGTWRPL and APIIGKPAPGFK) were identified.